Acquiescences effects in measuring attitudes towards immigrants : the case of Romania - Voicu, Bogdan; Șerban, Monica; Tudor, Elena; Deliu, Alexandra (Calitatea Vieții, 2013)
This papers tests for acquiescence effects on the attitudes towards immigrants. We employ the case of Romania, a country with very little incoming migration, but with an important outgoing flow. This makes the respondents less exposed to interaction with immigrants, but with a high probability to know emigrants, and to have emigrants in the immediate social network and/or kinship. Due to the lack of interaction with immigrants, we expected to discover significant impact of acquiescence on attitudes towards immigrants. This is supported with empirical evidences, using the Romanian EVS 2008 data and OLS models. We also show out that the net acquiescence score performs best in such models, overcoming the utility of other indicators of acquiescence.